2019
DOI: 10.1039/c9ra08763j
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and electroactive phase adjustment of Ag-doped poly(vinylidene fluoride) (PVDF) films

Abstract: The ratio of γ- and β-phases of Ag-doped poly(vinylidene fluoride) films was controlled by removing Ag+ using a washing process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…Based on the overall data, we can conclude that by increasing the Ag-BT hybrid filler addition in the composites, the formation of the polar structure β and γ phases of PVDF is promoted, although the major phase remains the α-polymorph. An increase of the electroactive β and γ phases of PVDF as induced by the presence of silver inclusions was also reported in recent literature [ 43 , 44 ]. A detailed nanoscale experimental study combined with DFT calculations demonstrated that the mechanism favoring the formation of polar phases resulted from a polar interfacial coupling between the filler and the molecular chains of the polymer promoting specific polar arrangements, i.e., the presence of electroactive phases [ 44 ].…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…Based on the overall data, we can conclude that by increasing the Ag-BT hybrid filler addition in the composites, the formation of the polar structure β and γ phases of PVDF is promoted, although the major phase remains the α-polymorph. An increase of the electroactive β and γ phases of PVDF as induced by the presence of silver inclusions was also reported in recent literature [ 43 , 44 ]. A detailed nanoscale experimental study combined with DFT calculations demonstrated that the mechanism favoring the formation of polar phases resulted from a polar interfacial coupling between the filler and the molecular chains of the polymer promoting specific polar arrangements, i.e., the presence of electroactive phases [ 44 ].…”
Section: Resultssupporting
confidence: 68%
“…The dielectric, ferroelectric, and piezoelectric properties are enhanced by the conformations with a larger dipole moment, i.e., in the electroactive phases β and γ. The phase composition was observed to be sensitive to the processing strategy and parameters, to co-polymerisation [ 41 , 42 ], or by nanofiller additions [ 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…We prepared PVDF particles used as cores in spherical particles of uniform size, as shown in Figure b, through semibatch emulsion polymerization . Previous studies have confirmed that PVDF is induced into the β-phase by cations . Unlike conventional PVDF, where ammonium persulfate is used as an initiator, a large portion of the PVDF particles in the synthesis process have a β-phase (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…38 Previous studies have confirmed that PVDF is induced into the β-phase by cations. 39 Unlike conventional PVDF, where ammonium persulfate is used as an initiator, a large portion of the PVDF particles in the synthesis process have a β-phase (Figure S1). To block the conductive pathway near the core PVDF in the β-phase, the silica shell was coated through use of the sol−gel method, as shown in Figure 1a.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…[1][2][3][4] It can be stabilized in its distinct polymorphs, α (TGTG′, form II), β (TTTT, form I), γ (T 3 GT 3 G′, form III), δ and ε depending on the molecular chain conformation during the fabrication process. 3,[5][6][7][8][9][10] Various techniques and treatments such as mechanical (stretching), 11,12 thermal (heat temperature), 13 electrical (poling process) 14 and chemical treatments (effect of solvents or other additives) 9,[15][16][17][18][19] during the processing of PVDF affect the molecular phase stabilization in it and hence, the final properties. Among its all forms, β-PVDF is the most electroactive showing good ferro/piezoelectric properties.…”
Section: Introductionmentioning
confidence: 99%